A zonally averaged, coupled ocean-atmosphere model for paleoclimate studies - Stocker, Thomas F.; Wright, Daniel G.; Mysak, Lawrence A. (American Meteorological Society, 1992)
A zonally averaged ocean model for the thermohaline circulation is coupled to a zonally averaged, one-layer energy balance model of the atmosphere to form a climate model for paleoclimate studies. The emphasis of the coupled model is on the ocean's thermohaline circulation in the Pacific, Atlantic, and Indian oceans. Each basin is individually resolved, and they are connected by the Southern Ocean through which mass, heat, and salt are exchanged. Under present-day conditions, the global conveyor belt is simulated: deep water is formed in the North Atlantic and the Southern Ocean, whereas both Pacific and Indian oceans show broad upwelling. Latitude-depth structures of modeled temperature and salinity fields, as well as depth-integrated meridional transports of heat and freshwater, compare well with estimates from observations when wind stress is included. Ekman cells are present in the upper ocean and contribute substantially to the meridional fluxes at low latitudes, bringing them to close agreement with observed estimates. The atmospheric component of the coupled climate model consists of a classical, time-dependent energy balance model; the seasonal cycle is not included. Observations and the ocean-to-atmosphere fluxes at steady state are used to determine the net downward shortwave radiation, constant greybody emissivity, eddy diffusivity parameterizing the meridional energy fluxes in the atmosphere, and evaporation and precipitation over the individual ocean basins. When the two components are coupled after being spun up individually, the system remains steady provided that no intermittent convection is present in the ocean model. If internmittent convection is operating, the coupled model shows systematic deviations of the surface salinity, which may result in reversals of the thermohaline circulation. This climate drift can be inhibited by removing intermittent convection prior to coupling. The climate model is applied to investigate the effect of excess freshwater discharge into the North Atlantic, and ...